Ocean Earth : 1980 bis heute. - Donga, Thomas; Rivkin, Harold; Tekampe, Heike; Weibel, Peter; Künstlerhaus, Graz (Graz : Neue Galerie am Landesmuseum Joanneum, 1993)
Beuys, Joseph ; Smithson, Robert ; Matta-Clark, Gordon ; Fend, Peter ; Fitzgibbon, Colen ; Holzer, Jenny ; Nadin, Peter ; Prince, Richard ; Winters, Robin ; Jansen, Heather ; Mosher, Kärsten ; Oppenheim, Dennis ; Sharits, Paul ; Staehle, Wolfgang ; Günther, Ingo ; Lehmann, Gregory ; Vaterlaus, Eve ; Waltemath, Joan
Duits
Engels
Ocean Earth - For A World Which Works, Künstlerhaus Graz, Februar/März 1993
boek